Cognitive and affective motivation in conceptual modelling - Furtado, Antonio L.; M. Ciarlini, Angelo E. (Revista Colombiana de Computación, 2002)
A proposal is presented towards the extension of conceptual models of information systems, in order to allow specification and simulation of the behaviour of agents with an adequate degree of realism. Our method is mainly based on rules to infer the goals of agents from situations holding at given states. In this paper, we argue that the rules should take into account both cognitive and affective characteristics, as can be conveyed, for the various agents, by their individual profiles and current internal states. Such characteristics should also influence the choice of strategies to handle goal interferences in multi-goal/multi-agent environments. Keywords: Conceptual Modelling, Simulation, Multi-Agents, Affective Motivation, Goal Interferences